Impact and Risk of Moral Injury Among Deployed Veterans: Implications for Veterans and Mental Health - Boscarino, Joseph A.; Adams, Richard E.; Wingate, Tiah J.; Boscarino, Joseph J.; Urosevich, Thomas G.; Hoffman, Stuart N.; Kirchner, H. Lester; Figley, Charles R.; Nash, William P. (Frontiers in Psychiatry, 2022)
The impact of “moral injury” (MI) among veterans, defined as actions in combat that violate a veteran’s moral beliefs and results in psychological distress, has been a concern. MI involves distress over violations of core beliefs often followed by feelings of guilt and conflict and is common among those with severe PTSD symptoms. While the psychological impact of PTSD is well documented among veterans, this is less so with respect to MI. We studied MI among 1,032 deployed veterans who were outpatients in a large non-profit multi-hospital system in central Pennsylvania. The study included active duty and Guard/Reserve members, as well as veterans who were not VA service users. Our hypothesis was that, controlling for other risk factors, veterans with MI would have current mental disorders. Our secondary hypothesis was that MI would be associated with other health problems, including chronic pain, sleep disorders, fear of death, anomie, and use of alcohol/drugs to cope post deployment. Most veterans studied were deployed to Vietnam (64.1%), while others were deployed to post-Vietnam conflicts in Iraq and Afghanistan and elsewhere. Altogether, 95.1% of the veterans were male and their mean age was 61.6 years (SD=11.8). Among the veterans, 24.4% had high combat exposure, 10.9% had PTSD, 19.8% had major depressive disorder, and 11.7% had a history of suicidal thoughts. Based on the Moral Injury Events Scale (MIES), 25.8% had high MI post deployment, defined as at or above the 75th percentile. Results show that high MI among veterans was associated with current global mental health severity and recent mental health service use, but not suicidal thoughts. In addition, MI was also associated with pain, sleep disorders, fear of death, anomie, use of alcohol/drugs to cope post deployment, and poor unit support. Deployed veterans with MI are more likely to have current mental health disorders and other health issues and psychological problems after deployment. Further research is advised related to the screening, assessment, treatment, and prevention of MI among veterans after warzone exposures.